2000
DOI: 10.1210/jcem.85.6.6651
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Hypertension in Familial Hyperaldosteronism Type I: Relationship to Gender and Degree of Biochemical Disturbance1

Abstract: In familial hyperaldosteronism type I (FH-I), inheritance of a hybrid 11␤-hydroxylase/aldosterone synthase gene causes ACTHregulated aldosterone overproduction. In an attempt to understand the marked variability in hypertension severity in FH-I, we compared clinical and biochemical characteristics of 9 affected individuals with mild hypertension (normotensive or onset of hypertension after 15 yr, blood pressure never Ͼ160/100 mm Hg, Յ1 medication required to control hypertension, no history of stroke, age Ͼ18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
1
5
0
2
Order By: Relevance
“…A support of this interpretation is our preliminary observation that the plasma levels of Ang II and of aldosterone are both increased in the Agt 2͞2 animals to about 1.4 times their levels in wild-type animals. Human patients with glucocorticoid-remediable aldosteronism carry an additional chimeric gene that fuses the regulatory sequences of steroid 11␤ hydroxylase to the coding sequences of AS; these patients have 1.5 times plasma aldosterone levels and are hypertensive (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…A support of this interpretation is our preliminary observation that the plasma levels of Ang II and of aldosterone are both increased in the Agt 2͞2 animals to about 1.4 times their levels in wild-type animals. Human patients with glucocorticoid-remediable aldosteronism carry an additional chimeric gene that fuses the regulatory sequences of steroid 11␤ hydroxylase to the coding sequences of AS; these patients have 1.5 times plasma aldosterone levels and are hypertensive (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…It is also probable that other genes involved in blood pressure regulation influence the phenotypic expression of the hybrid gene. Our two oldest normotensive individuals with FH‐I demonstrated PRA levels that differed from those of other affected subjects, with one showing basal levels that were high/ normal and the other having levels that were suppressed basally, but showed a much brisker rise in response to correction of hyperaldosteronism by dexamethasone 73,74 . Neither had ever received diuretics nor had 24 h urinary sodium levels suggestive of marked dietary salt restriction to explain increased PRA levels or responsiveness.…”
Section: Familial and Normotensive Primary Aldosteronismmentioning
confidence: 79%
“…Whereas some of these individuals are still in childhood and may become hypertensive with time, many have remained normotensive into adulthood. Among our series of patients with FH‐I, females have been relatively protected against the development of hypertension 74 . Five of six individuals who have remained normotensive into their third decade of life and all three subjects who are still normotensive in their fifth decade are females.…”
Section: Familial and Normotensive Primary Aldosteronismmentioning
confidence: 85%
“…In our largest family, one affected male who had been severely hypertensive since the age of 13 years died at 21 years of haemorrhagic stroke, whereas a 45‐year‐old affected female has remained normotensive. Seeking explanations for this marked variability in phenotypic expression, we found that: (i) females appear to be relatively protected, being less likely to have severe hypertension and tending to live longer than males; 26 (ii) even normotensive individuals demonstrate biochemical evidence of hybrid gene expression, with suppressed PRA, high aldosterone/PRA ratios and urinary 18‐oxo‐cortisol levels and tight correlation of circadian aldosterone levels with cortisol rather than PRA, suggesting that lack of hypertension is not explained by lack of expression of the hybrid gene; 27 and (iii) the degree of hybrid gene expression may help determine hypertension severity, because patients with more severe hypertension have tended to demonstrate lower plasma potassium and higher urinary 18‐oxo‐cortisol and recumbent plasma aldosterone levels 26 …”
Section: Familial Hyperaldosteronism Type Imentioning
confidence: 88%
“…The severity of hypertension varies widely in FH‐I, even within the same family 8,26 . In our largest family, one affected male who had been severely hypertensive since the age of 13 years died at 21 years of haemorrhagic stroke, whereas a 45‐year‐old affected female has remained normotensive.…”
Section: Familial Hyperaldosteronism Type Imentioning
confidence: 89%